2016
DOI: 10.1097/aud.0000000000000275
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Pure-Tone Threshold Shifts Caused by Tympanic Membrane Electrodes

Abstract: Objective To determine if tympanic membrane (TM) electrodes induce behavioral pure tone threshold shifts. Design Pure tone thresholds (250–8000 Hz) were measured twice in test (n=18) and control (n=10) groups. TM electrodes were placed between first and second threshold measurements in the test group, whereas the control group did not receive electrodes. Pure tone threshold shifts were compared between groups. The effect of TM electrode contact location on threshold shifts was evaluated in the test group. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…TM electrodes were inserted into the right ear canal of each subject and advanced until the TM was contacted, which was verified by subject report of the occlusion effect and by monitoring electrode impedance changes until they were consistently ≤7 kΩ on the Intelligent Hearing Systems bio-amplifier (Ferraro, 2010). Further confirmation of electrode contact with the TM was indicated by areas of acute redness and accumulation of electrode gel observed otoscopically after TM electrodes were removed at the end of each testing session (see Smith et al, 2016, Figure 1). Each electrode was held in place throughout the session by a 13 mm ER3-14A foam ear tip coupled to the ER-3A insert earphone.…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…TM electrodes were inserted into the right ear canal of each subject and advanced until the TM was contacted, which was verified by subject report of the occlusion effect and by monitoring electrode impedance changes until they were consistently ≤7 kΩ on the Intelligent Hearing Systems bio-amplifier (Ferraro, 2010). Further confirmation of electrode contact with the TM was indicated by areas of acute redness and accumulation of electrode gel observed otoscopically after TM electrodes were removed at the end of each testing session (see Smith et al, 2016, Figure 1). Each electrode was held in place throughout the session by a 13 mm ER3-14A foam ear tip coupled to the ER-3A insert earphone.…”
Section: Methodsmentioning
confidence: 96%
“…Threshold was defined as the lowest presentation level at which three positive responses occurred. These measurements were made without electrodes in the ear canal, as our previous work demonstrated that TM electrode contact with the eardrum can influence audiometric thresholds, particularly to low frequencies (Smith et al, 2016). Average behavioral thresholds were 32 dB ppeSPL and 30 dB ppeSPL for clicks and chirps, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The most common way to identify electrode placement is after measurements are done and remaining electrode gel and irritation is visualized with otoscopy. Smith et al ( 2016 ) found that electrode placement mostly affects measurements from low-frequencies when an insert-earphone is used, a possible influence on our measurements to 500 Hz.…”
Section: Discussionmentioning
confidence: 90%
“…At least two traces were recorded to ensure repeatability of the SP and AP responses. Because of recording ECochG and ABR to three different electrode types, testing took place on two separate days for each participant to avoid any hearing threshold shifts from the TM electrode placement 22,23 that might affect the measurements. This was also useful to evaluate the reproducibility and reliability of the measures, as evaluated later the results section.…”
Section: Methodsmentioning
confidence: 99%